2016
DOI: 10.1002/anie.201605337
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Six Products from a Single Indolyl α‐Diazocarbonyl Precursor

Abstract: Indolyl α-diazocarbonyls can be selectively cyclized to give six distinct products through the careful choice of catalyst and reaction conditions. A range of catalysts were used, including complexes of Rh(II) , Pd(II) , and Cu(II) , as well as SiO2 , to promote diazo decomposition and subsequent cyclization/rearrangement through a range of mechanistic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…In all cases the calculated transition states for carbon–carbon bond formation are located at low energy (<41 kJ mol –1 with respect to the reference state) and the C–C bond formation ( 1 → 2 ) step was calculated to be almost barrierless. These results, and others, 10 17 demonstrate the synthetic versatility of 1 as a framework to access a range of important structural motifs.…”
Section: Introductionsupporting
confidence: 69%
“…In all cases the calculated transition states for carbon–carbon bond formation are located at low energy (<41 kJ mol –1 with respect to the reference state) and the C–C bond formation ( 1 → 2 ) step was calculated to be almost barrierless. These results, and others, 10 17 demonstrate the synthetic versatility of 1 as a framework to access a range of important structural motifs.…”
Section: Introductionsupporting
confidence: 69%
“…Communications product 4a was much more surprising,w ith the structure of this product confirmed by X-ray crystallography. [14] It was found that the selective synthesis of either product could be achieved, with the reaction outcome being dependent on the presence of air in the reaction. By switching the reaction solvent from CH 2 Cl 2 to chloroform, reducing catalyst loading to 5mol %, and performing the reaction under oxygen-free conditions, 3a was isolated in 92 %y ield (Scheme 1).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Both product structures were confirmed by X-ray analysis. [14] Next, the palladium(II)-and copper(II)-catalyzed reactions were optimized, thus allowing selective formation of the C2-annulated product 5aand carbazole 6ausing Pd(MeCN) 4 -(BF 4 ) 2 (5 mol %) and Cu(OTf) 2 (20 mol %), respectively (Scheme 4). [18,19] Ak ey difference between these reactions is that it is necessary to perform the carbazole-forming reaction under oxygen at 50 8 8C.…”
Section: Communicationsmentioning
confidence: 99%
“…[23] Moreover,w ithin af ragment-based drug discovery context,t here have been recent calls for the design and synthesis of novel compounds that feature multiple 3D growth vectors whilst incorporating polar functionality form olecular recognition. [24] In response to this, notable examples of efficient syntheses of diverse sp 3 -rich libraries have been recently published, [25][26][27][28][29][30][31][32] however there is stilla no utstanding need for diversel ibraries featuring this key N-containing quaternary stereocenter motif.…”
Section: Introductionmentioning
confidence: 99%